Carcinoma espinocelular en hospitales públicos de la Región Metropolitana de Chile: análisis de la localización anatómica, género y edad - Zemelman D., Viviana; Ramírez R., Constanza; Alvo V., Andrés; Aedo S., Alberto; Feldman F., Marcos (Revista Hospital Clínico Universidad de Chile, 2010)
Cutaneous squamous cell carcinoma (SCC) is the second most common skin cancer; its incidence is increasing in the last decades worldwide. The purpose of this study was to analyze 1320 SCC (716 males and 604 females) from five hospitals of Santiago. The tumours were studied by gender, anatomical localization and age of the patient. For this, 600.000 histopathological reports were reviewed (1992-2001). SCC was more frequent in males than females and also more frequent in older people. The average age was 72.1 +/-14.3 years old in females and 69.5+/-13.2 years old in males. The most frequent anatomical locations in females were the face (51.2%), lower extremities (13.9%) and genitals (12.1%). The most frequent anatomical locations in males were the face (62.4%); genitals (9.8%) and lower extremities (8.1%). More number of facial SCC was observed in males than in females; however; more SCC in lower extremities was observed in females than in males. In relation to age, CEC was more frequent in males in the 50-59 and 70-79 years old groups, however; CEC was more frequent in females older than 80 years old. The study of 1320 SCC tumours allows us to analyze risk groups in the Chilean population that help to direct future skin cancer prevention campaigns in Chile.